Assessing safety culture in NICU: psychometric properties of the Italian version of Safety Attitude Questionnaire and result implications. Issue 2 (23rd October 2015) - Zenere, Alessandra; Zanolin, M. Elisabetta; Negri, Roberta; Moretti, Francesca; Grassi, Mario; Tardivo, Stefano
Abstract: Rationale, aims and objective: Neonatal intensive care units (NICUs) are a high‐risk setting. The Safety Attitude Questionnaire (SAQ) is a widely used tool to measure safety culture. The aims of the study are to verify the psychometric properties of the Italian version of SAQ, to evaluate safety culture in the NICUs and to identify improvement interventions. Method: A cross‐sectional study was conducted in 6 level III NICUs. The SAQ was translated into Italian and adapted to the context, a confirmatory factor analysis (CFA) was performed to validate the questionnaire. Results: 193 questionnaires were collected. The mean response rate was 59.7% (range 44.5%–95.7%). The answers were analysed according to six factors: f1 – teamwork climate, f2 – safety climate, f3 – job satisfaction, f4 – stress recognition, f5 – perception of management, f6 – working conditions . The CFA indexes were adequate (McDonald's omega indexes varied from 0.74 to 0.94, the SRMR index was equal to 0.79 and the RMSEA index was 0.070, 95% CI = 0.063–0.078). The mean composite score was 57.6 (SD 17.9), ranging between 42.3 and 69.7 on a standardized 100‐point scale. We highlighted significant differences among units and professions ( P < 0.05). Conclusions: The Italian version of the SAQ proved to be an effective tool to evaluate and compare the safety culture in the NICUs. The obtained scores significantly varied both within and among the NICUs. The organizational and structural characteristics of the involved hospitals probably affect the safety culture perception by the staff.